Assessment of correlation of serum high-sensitive C-reactive protein, urinary albumin-to-creatinine ratio, and lipid profile in diabetics - Shweta Kumari; Beena Singh (Wolters Kluwer Medknow Publications, 2021)
Background: This study aimed to measure the level of serum high-sensitive C-reactive protein (hs CRP), urinary albumin-to-creatinine ratio (ACR), lipid profile, and their association in diabetics. Methodology: One hundred and fifty diabetic patients were classified into three groups of 50 each. Group I were newly diagnosed with <5 years of diabetes, Group II were those having 5-10 years of diabetes, and Group III were diabetics with more than 10 years of diabetes. Lipid profile, hs-CRP level, and ACR were measured. Results: There was a correlation between hS CRP and ACR and triglyceride in Group I, hS CRP with ACR and triglyceride in Group I. In group II hS CRP showed significant correlation with ACR whereas in Group III significant correlation was observed with ACR, low density lipoprotein (LDL) and cholesterol. Conclusion: The level of hS CRP and ACR was found to be higher in patients with a longer duration of diabetes.